Ittihad al-Majlis dalam Perspektif Mazhab Syafi’iyah dan Hanafi’iyah: Kajian Fikih Kontemporer - Ahmad Waffa Kamal Sahir; Muhammad Farhan Habibi; Siti Masnu’ah; Luthfiyah Luthfiyah; M Abdul Rahman Hakim (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the concept of ittihadul dewan in ijab qabul according to the Syafi'i and Hanafi schools, and its impact on technological progress. The marriage contract is based on the element of mutual consent, which is manifested through ijab qabul as the main requirement for the validity of the contract. This study uses a library research method with data collection techniques based on literature reviews. The results of the study indicate that according to scholars of the Syafi'i school, a marriage contract carried out via telephone or other communication media is invalid because it does not meet the requirements of ittihadul dewan which requires physical presence in one place. On the other hand, scholars of the Hanafi school consider such a contract valid, because they interpret ittihadul dewan based on the continuity of time, even though the parties to the contract are in different places.